2021
DOI: 10.1097/nnd.0000000000000732
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Bedside Nurse in Research and Quality Improvement

Abstract: Nurses are expected to participate in research and scholarly inquiry; despite ongoing attempts, the practice-research gap continues to be fraught with significant barriers. System strategies have not addressed concerns at the individual nurse level. Given the implications on quality and safety, focusing on identification of individual nurse strategies should be an important focus of attention for nursing leaders and researchers. This article seeks to describe barriers, potential solutions, and implications for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Nurse engagement in QI efforts is directly linked to improved patient outcomes (Dempsey & Assi, 2018). Albanese et al (2010) reported that engaging the nursing workforce in QI starts with education; likewise, exposure is the first step to increase motivation and improve attitudes toward QI (Mulkey, 2021). Participants who identified they enjoyed the escape room stated, “I think we were in survival mode (during the pandemic), and you can’t sit back and enjoy what you’ve done until you’ve seen what you’ve done” and “You don’t always see opportunities to learn and have fun at the same time.”…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurse engagement in QI efforts is directly linked to improved patient outcomes (Dempsey & Assi, 2018). Albanese et al (2010) reported that engaging the nursing workforce in QI starts with education; likewise, exposure is the first step to increase motivation and improve attitudes toward QI (Mulkey, 2021). Participants who identified they enjoyed the escape room stated, “I think we were in survival mode (during the pandemic), and you can’t sit back and enjoy what you’ve done until you’ve seen what you’ve done” and “You don’t always see opportunities to learn and have fun at the same time.”…”
Section: Discussionmentioning
confidence: 99%
“…However, organizations often have limited resources available that motivate and engage clinical nurses in QI processes such as identifying problems, recommending improvements, collecting data, and evaluating progress. These limitations can be identified as system barriers related to a lack of education, mentorship, prioritization, and time (Mulkey, 2021). Nurses must possess the knowledge, skills, and attitudes required to improve patient outcomes while using data to track improvements.…”
mentioning
confidence: 99%
“…As we continue to deal with a nursing shortage, offering variety and flexibility is vital to recruitment and retention 18. Nursing is the one profession that's a constant at the bedside, and engagement of nurses can drive practice changes, increased quality, and overall nursing satisfaction 19. Providing the dual-role opportunity allows the nurse to become engaged in multiple areas and see things from a more global perspective.…”
Section: Benefitsmentioning
confidence: 99%
“…8 Because of their continuous bedside presence, nurses offer a unique perspective in identifying barriers to patient research implementation including access to resources to support competency and engagement in research. 9 Increased resources for RN research are linked to more research activities such as higher numbers of nurse-led studies and nurse-authored, peer-reviewed publications. 10 Infrastructures that increase the likelihood of RN involvement in research in a healthcare setting include utilization of an endorsed framework for scholarly inquiry, 11 formal programs to teach and train research skills, mentorship support, and protected, paid time to allow RNs to work on research in lieu of other job duties.…”
mentioning
confidence: 99%
“…Because of their continuous bedside presence, nurses offer a unique perspective in identifying barriers to patient research implementation including access to resources to support competency and engagement in research 9 . Increased resources for RN research are linked to more research activities such as higher numbers of nurse-led studies and nurse-authored, peer-reviewed publications 10 .…”
mentioning
confidence: 99%